Pengaruh Green Banking Disclosure, Efisiensi Operasional, dan Capital Adequacy Ratio Terhadap Profitabilitas pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Simanjuntak, Nerlin P.; Lamria Sagala; Rimky Mandala Putra Simanjuntak; Merry Anna Napitupulu (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2026)
This study aims to examine and analyze the effect of Green Banking Disclosure, Operational Efficiency, and Capital Adequacy Ratio on Profitability in banking sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. This study uses a quantitative approach with secondary data sourced from annual reports and sustainability reports of banking companies. The sampling method used is purposive sampling, resulting in 18 banking companies as samples with 73 observations after outlier treatment. The data analysis method used is multiple linear regression analysis processed with IBM SPSS Statistics 26. The results show that partially Green Banking has a negative and insignificant effect on Profitability, Operational Efficiency (BOPO) has a negative and significant effect on Profitability, and Capital Adequacy Ratio (CAR) has a positive and insignificant effect on Profitability. Simultaneously, Green Banking, Operational Efficiency, and Capital Adequacy Ratio have a significant effect on Profitability. The coefficient of determination (Adjusted R²) is 87.7%, meaning these three variables together explain 87.7% of the variation in Profitability (ROA), while the remaining 12.3% is influenced by other variables not included in the model.